Historiografi Islam Cirebon (Kajian Manuskrip Sejarah Islam Cirebon) - Alfan Firmanto (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2015)
Cirebon is one of the centre of Islamic propagation in West Java that preserved any historical evidences. These evidences are not only in the form of physical lagacies such as mosques, palaces, tombs, and old boarding schools, but also non-physical ones such as unique tradition compounding of Java and Islam which was still maintained by the people up to present.Another important source of Islamic history of Cirebon was written sources consisting of a huge numbers of classical texts or manuscripts. Based on such manuscripts it will be understood of haw the role and function of Cirebon inthe past time. For that purpose, it is important to conduct research on the history of Cirebon bay mean of using the manuscripts as the main sources.